Tourism management guidelines for the Erongo coastal region, Namibia - Kilele, Felicia Chepkurui (Department of Environmental and Geographical Science, 2023)
Coastal areas are important as they contain a disproportionately large share of global urban areas; industrial activities; pollution sources; food production; tourism; biodiversity and poverty (Olsen, 1993: 201 ). Throughout much of the world, these areas face considerable population and development pressures. The world's population is projected to grow exponentially from 4.1 billion in 1990 to 6.2 billion by the year 2000. Currently, more than 50% of the world's population lives within 60 kms of the coastline (World Bank, 1993a: 4). A concern resulting from these pressures is degradation of coastal resources. The degrading condition of the coastal resources raises concerns as to the long-term capacity of coastal ecosystems to provide for sustainable development (Olsen, 1993: 20 I). Thus industries that are highly dependent on coastal resources, such as tourism, are particularly vulnerable.